(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
Musanga cercropioides is a plant that is used to treat a variety of ailments in many African countries. However, just a few studies have been conducted to assess the toxicity of the various sections of this plant. The goal of this study was to determine the toxicity profile of Musanga cercropioides methanol leaf extract in albino rats. Lorke’s approach was used to conduct an acute toxicity study. In the first phase, nine (9) albino rats were randomly divided into three (3) groups of three (3) animals each. Each of the animals were orally administered 10,100 and 1000 mg/kg body weight of the extract. In the second phase, twelve (12) animals were used, which were divided into four groups of three (3) animals each. The first three groups received single doses of 1500, 3000, and 5000 mg/kg, respectively, while the fourth group which served as a control was given distilled water orally. After observation for 14 days, no signs of mortality were identified. The maximum dose supplied (5000 mg/kg body weight) did not affect the test animals’ mortality or general behavior. When the treated groups were compared to the control groups, there was no significant difference (p > 0.05) in biochemical markers, body weight, or relative organ weights of liver, kidney, heart, and spleen. These findings show that oral administration of Musanga cercropioides methanol leaf extract is safe at a dose of up to 5000 mg/kg body weight in Wistar albino rats.